Can Drug Courts Help to Reduce Prison and Jail Populations?. Issue 1 (May 2013) - Sevigny, Eric L.; Pollack, Harold A.; Reuter, Peter
Drug courts have been widely praised as an important tool for reducing prison and jail populations by diverting drug-involved offenders into treatment rather than incarceration. Yet only a small share of offenders presenting with drug abuse or dependence are processed in drug courts. This study uses inmate self-report surveys from 2002 and 2004 to examine characteristics of the prison and jail populations in the United States and assess why so many drug-involved offenders are incarcerated. Our analysis shows that four factors have prevented drug courts from substantially lowering the flow into prisons and jails. In descending order of importance, these are: drug courts' tight eligibility requirements, specific sentencing requirements, legal consequences of program noncompliance, and constraints in drug court capacity and funding. Drug courts will only be able to help lower prison and jail populations if substantial changes are made in eligibility and sentencing rules.